APPLICATION OF INTERACTIVE MEDIA AND DIGITAL MEDIA FOR THE REVITALIZATION OF THE MUSEUM POS INDONESIA - Sasangka Bhima Asmara; Didit Widiatmoko Soewardikoen; Hanif Azhar; Yanuar Rahman; Andreas Rio Adriyanto (Adisam Publisher, 2025)
Museum Pos Indonesia in Bandung has the potential to be a rich educational and historical tourism center, but faces challenges in attracting visitors, especially the younger generation, due to its conventional presentation and lack of utilization of digital technology. In the revitalization effort, an interactive technology-based design approach is seen as a solution to create a more engaging, informative, and relevant museum experience. This research applies a qualitative method with a Design Thinking approach, which includes five stages: empathize by conducting observations and interviews with visitors and managers, define to formulate the main problems of the museum, ideate in designing interactivity-based design solutions, prototype as a visualization of space and media, and test to test the effectiveness of the visitor experience. Digital interactive media such as touch screens, video mapping, augmented reality, and QR code-based audio systems are designed and adapted to visitor segmentation from children to adults. It is hoped that the results of this research will create a showroom atmosphere that is educative, inclusive and fun, and strengthen the position of Museum Pos Indonesia as a modern cultural institution that is able to adapt in the digital era.